2016
DOI: 10.1111/joor.12418
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a two‐step impression procedure for complete denture fabrication: a systematic review of the literature

Abstract: The literature has questioned the real need for some clinical and laboratory procedures considered essential for achieving better results for complete denture fabrication. The aim of this study was to review the current literature concerning the relevance of a two-step impression procedure to achieve better clinical results in fabricating conventional complete dentures. Through an electronic search strategy of the PubMed/MEDLINE database, randomised controlled clinical trials which compared complete denture fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
15
0
5
Order By: Relevance
“…Improvement of denture fabrication process as one of these important factors has been investigated in some previous studies. 4,22 Different occlusal schemes have been tested for CCDs. 2,7,13 BO was discussed in our pervious clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improvement of denture fabrication process as one of these important factors has been investigated in some previous studies. 4,22 Different occlusal schemes have been tested for CCDs. 2,7,13 BO was discussed in our pervious clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The occlusal scheme can affect denture retention, stability, occlusal force distribution, aesthetics, masticatory function, patient comfort and general patient satisfaction with dentures. [6][7][8] Review of the literature yielded 5 systematic reviews comparing different occlusal schemes in CCDs, but an account of lacking enough…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study that investigated the use of an abbreviated impression technique that used a one‐step impression with irreversible hydrocolloid and stick trays by predoctoral dental students in a dental school setting concluded that this method, compared to the two‐step procedure, decreased the number of treatment appointments without increasing the number of adjustments or reline procedures . Although there is not a large number of studies comparing the one‐ and two‐step methods, two systematic reviews suggested that the two‐step impression procedure is not mandatory for achieving clinical success considering both denture quality and patients' perception of treatment, and the use of simpler and less costly methods may be sufficient to serve the needs of the majority of patients . A recent Cochrane review by Jayaraman et al reported that most of the randomised clinical trials on this topic were judged as having high risk of bias and concluded that “there is no clear evidence that one technique or material has a substantial advantage over another for making complete dentures and removable partial dentures” …”
Section: Discussionmentioning
confidence: 99%
“…Whilst most classic textbooks, teaching and prosthodontist practice claim the critical importance of a detailed reproduction of the denture-bearing tissues using a two-step impression technique (a preliminary impression with irreversible hydrocolloid in a stock tray followed by a final impression using a custom tray and a variety of impression materials), 7 the results of clinical studies suggest that the two-step impression is not mandatory to ensure satisfactory stability, retention, support and effective function of the complete denture. 8 Simplified methods using a one-step procedure that includes only the preliminary impression with irreversible hydrocolloid and a stock tray have been reported to have similar results compared to the traditional method regarding patient-reported outcomes, masticatory efficiency and denture quality, [11][12][13][14][15] and have also been considered more cost-effective than the traditional method. 6 This study tested an intermediary alternative between the oneand two-step methods, performing a final impression similar to the clinical relining procedure combining a closed-and open-mouth procedure for the maxilla and mandible, respectively, with the try-in dentures being used as trays for making the final impression.…”
mentioning
confidence: 99%